A photosynthesis‐based two‐leaf canopy stomatal conductance model for meteorology and air quality modeling with WRF/CMAQ PX LSM. Issue 3 (6th February 2017) - Ran, Limei; Pleim, Jonathan; Song, Conghe; Band, Larry; Walker, John T.; Binkowski, Francis S.
Abstract: A coupled photosynthesis‐stomatal conductance model with single‐layer sunlit and shaded leaf canopy scaling is implemented and evaluated in a diagnostic box model with the Pleim‐Xiu land surface model (PX LSM) and ozone deposition model components taken directly from the meteorology and air quality modeling system—WRF/CMAQ (Weather Research and Forecast model and Community Multiscale Air Quality model). The photosynthesis‐based model for PX LSM (PX PSN) is evaluated at a FLUXNET site for implementation against different parameterizations and the current PX LSM approach with a simple Jarvis function (PX Jarvis). Latent heat flux (LH) from PX PSN is further evaluated at five FLUXNET sites with different vegetation types and landscape characteristics. Simulated ozone deposition and flux from PX PSN are evaluated at one of the sites with ozone flux measurements. Overall, the PX PSN simulates LH as well as the PX Jarvis approach. The PX PSN, however, shows distinct advantages over the PX Jarvis approach for grassland that likely result from its treatment of C3 and C4 plants for CO2 assimilation. Simulations using Moderate Resolution Imaging Spectroradiometer (MODIS) leaf area index (LAI) rather than LAI measured at each site assess how the model would perform with grid averaged data used in WRF/CMAQ. MODIS LAI estimates degrade model performance at all sites but one site having exceptionally old and tall trees. Ozone deposition velocity and ozone flux along with LH are simulated especially well by the PX PSN compared to significant overestimation by the PX Jarvis for a grassland site. Key Points: A coupled photosynthesis‐stomatal conductance model is implemented and evaluated for PX LSM in WRF/CMAQ The photosynthesis‐based model simulates latent heat as well as the current Jarvis functional approach in PX LSM The photosynthesis‐based model shows distinct advantages in simulating LH and ozone fluxes for grassland